Implementasi Profil Pelajar Pancasila di PKBM Insan Cerdas Indonesia - Wijoyo, Refina Rian Putri; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to determine the implementation of the independent curriculum for the Pancasila student profile of the mutual cooperation dimension in the waste management program at CLC Insan Cerdas Indonesia. This research uses a qualitative descriptive research method with a type of field research, where data analysis involves collecting data, condensing data, presenting data and drawing conclusions. This research uses data collection techniques with participant observation, in-depth interviews, and documentation. The results of the research show that the existence of a waste management program that is oriented towards the independent curriculum of Pancasila student profiles can foster the character of students studying in CLC Insan Cerdas Indonesia who are virtuous and have the character of Pancasila students, and can explore and increase the potential of students learning in accordance with existing dimensions and elements. in the Pancasila student profile. The application of the Pancasila student profile to waste management makes a substantial contribution to efforts to shape the attitudes and character of students and implement Pancasila values. Waste management activities at CLC Insan Cerdas Indonesia are considered to be able to increase the ability of learning residents to grow in self-awareness to protect the environment around them, as well as being able to foster mutual cooperation behavior.